A new method for mitigating frequency fluctuations in ships with electrical propulsion. (June 2022) - Payvand, B.; Hosseini, S.M. Hassan
Abstract: Electrical networks of ships have less generation capacity compared to conventional large power systems. This leads to high frequency fluctuations and maybe blackout, especially in ships with electrical propulsion. Fundamentally, all of these ships have load reduction ability in critical conditions. Normally, load reductions are initiated with a time delay and this leads to a high frequency drop. Furthermore, load reductions need a real-time load management technique which can be used to decrease misdiagnosis and miscalculation probability. In some cases, the frequency may not violate its predefined limits but it may have high fluctuations that lead to malfunction of the sensitive equipment especially in military applications. In this paper, after extracting an electromechanical model of the whole system, frequency is regulated continuously by adding a frequency controller. Basic controller of the propulsion drive is investigated using the direct torque control (DTC) method. The frequency controller is designed to have minimum effect on normal operation of the drive and contributes in mitigating fluctuations only when response of the diesel generators is poor. Highlights: Using of electrical propulsion systems as a flywheel for mitigating of frequency fluctuations. Electromechanical modeling of the ships with electrical propulsion have been presented. Representing the continuous monitoring and controlling of the frequency with the help of the propulsion drivers.